Influence of damping and fluid loading on the plate vibration control - LENIOWSKA, Lucyna (Archives of Acoustics, 2008)
The aim of this paper is to present the effect of acknowledging viscous damping, structural internal damping and fluid loading on active vibration control of a circular plate in case of axially symmetrical vibrations. It was assumed that a planar vibrating structure located in a finite baffle and interacting with fluid is driven by a periodic force with constant amplitude, so the structure radiates the acoustic waves into a surrounding fluid and the axially-symmetrically located circular piezoelectric actuators are used to reduce its vibrations. For the purpose of control strategy designing process the continuous model derived from physical principles for the system under consideration has been developed. Next, the linear state model was obtained by reduction and approximation of the continuous model using the orthogonal series method. After that, the acquired model was used to produce body plots and to solve corresponding Riccati equation. Obtained control forces led to significant reduction of the plate vibration and attenuation of accompanied acoustic waves. The simulations of the active cancellation of the plate vibrations were made with a Simulink/Matlab computer program.